1980
DOI: 10.1073/pnas.77.12.7000
|View full text |Cite
|
Sign up to set email alerts
|

Novel RNA polymerase sigma factor from Bacillus subtilis.

Abstract: A modified form of Bacillus subtifis RNA polymerase (RNA nucleotidyltransferase) has been isolated that exhibits distinctive transcriptional specificity. This modified enzyme transcribes two cloned genes from the purA-cysA region of the B. subtilis chromosome whose expression in vivo is associated with the process of sporulation. Neither of these genes is transcribed by tie usual form of B. subtilis RNA polymerase holoenzyme containing a a factor of 55,000 daltons (I4 The modified RNA polymerase lacks -55 but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
246
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(252 citation statements)
references
References 28 publications
5
246
1
Order By: Relevance
“…Therefore, orf1 appears to be in a different operon. It should be pointed out then that a consensus promoter sequence was found in the upstream of btrR1 (Figure 1) [23]. Thus, an operon starting the btrR1 gene was envisioned to be the butirosin biosynthetic gene cluster.…”
Section: Extended Analysis Of Btr Gene Clustermentioning
confidence: 99%
“…Therefore, orf1 appears to be in a different operon. It should be pointed out then that a consensus promoter sequence was found in the upstream of btrR1 (Figure 1) [23]. Thus, an operon starting the btrR1 gene was envisioned to be the butirosin biosynthetic gene cluster.…”
Section: Extended Analysis Of Btr Gene Clustermentioning
confidence: 99%
“…Our in vitro studies revealed that transcription from the P1 promoter is dependent on the primary factor SA , while that of the P3 promoter is dependent on SB . As determined by primer extension studies, the 5 end of the SB -initiated mRNA synthesized in vitro from the sar P3 promoter is in agreement with the 5 end of the cellular RNA.In prokaryotes, several factors coexist in cells (19,22,24). The transcription factors evolutionarily related to Escherichia coli 70 are subdivided into two groups (15).…”
mentioning
confidence: 95%
“…B , identified in sporulating Bacillus subtilis, is the first member of the alternate factors to be reported in prokaryotes (20,21). Much has been learnt recently about the regulation of expression of the sigB operon and the modulation of the function of the SigB ( B ) protein in response to changing stress (entry into stationary growth phase, nutrient depletion, and presence of uncouplers of oxidative phosphorylation) and environmental stress (heat shock and osmotic shock) in B. subtilis (2,6,8,22,36,37,41).The emergence of multiple-drug-resistant, highly pathogenic strains of Staphylococcus aureus poses a serious threat for human and animal health management of infected subjects. S. aureus causes a number of infections ranging from superficial skin abscesses to life-threatening systemic diseases (e.g., toxic shock syndrome and osteomyelitis) (17,25,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B is a secondary sigma factor of Bacillus subtilis (14). Genes that rely on B for their expression are induced when B. subtilis ceases exponential growth in rich, sporulation-suppressing media or is exposed to any of several environmental insults (e.g., heat, salt, or ethanol) (2, 4, 7-10, 16, 25, 26).…”
mentioning
confidence: 99%